THE DEGRADATION OF DIESEL OIL BY CONSORTIUM OF BACTERIA IN SHAKEFLASK CULTURES - -, Ciawi; R., Safitri; N.W., Suniti; Y. P., Sahanggamu; I.D., Dharmawibawa; I.G.P, Wirawan (Bumi Lestari, 2012)
Diesel fuel is widely used in manufacturing and transportation industries. Its production, transportation, use and disposal have the risk to contaminate the environment. In the other hand contaminated site usually can produce some microorganisms, through natural selection, that can utilize the hydrocarbons as source of energy and food thus clean the environment itself. For bioremediation purposes, 14 isolates of diesel oil degrading bacteria from Bandung, Jakarta, and Bali has been employed for diesel oil degradation. These 14 isolates, together with other variables, e.g. pH, Pb, sucrose and urea, were plotted in 23x24 matrixes of Plackett and Burman statistical method. Fermentation was carried out in batch cultures for 14 days. The results showed that 9 isolates and the availability of sucrose and higher initial pH have a positive/stimulatory effect on diesel oil biodegradation, 5 of which were very significant (99.99%), whereas 1 isolate has inhibitory effect (-98%). The results also revealed that 8 isolates, higher initial pH, and availability of urea have stimulatory effect on culture growth (more than 90% significant). The present of Pb in medium inhibit both growth and the degradation of diesel oil, although the effect was not significant (less than 60%).
Keywords: biodegradation, diesel oil, bacteria isolates, shakeflask cultures